2020
DOI: 10.1002/chem.202002603
|View full text |Cite
|
Sign up to set email alerts
|

Dicarba[26]hexaporphyrinoids(1.1.1.1.1.1) with an Embedded Cyclopentene Moiety—Conformational Switching

Abstract: Incorporation of cyclopentene fragments into a skeletono fp arental[ 26]hexaphyrin(1.1.1.1.1.1) afforded extended carbaporphyrinoids:3 1,34-dicarbahexa[26]chlorin and its derivatives:t he first externally substituted by ethoxy and 2,4,6-trimethylbenzylidene groups and the second one formed by selective oxidation of one cyclopentenering. Macrocycles adopt dumbbell-shaped conformationsw ith two meso hydrogen atoms located inside the macrocyclic cavity. Protonation of 31,34-dicarba[26]hexachlorins provided dicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Thus, the C(21)H 2 resonance with the intensity of two hydrogens, scalar coupled to H(2,3), has been identified at −7.43 ppm. The HSQC experiment reveals the tetrahedral nature of this carbon consistently with its 13 C chemical shift equal to 28.4 ppm. The analogous protonation of the internal C( 21) carbon has been previously detected for 21-carba-23-thiaporphyrin, 23 or β-alkylated 21-carbaporphyrin, 19 benzocarbaporphyrin, 49 and N-confused porphyrin.…”
Section: +mentioning
confidence: 75%
See 3 more Smart Citations
“…Thus, the C(21)H 2 resonance with the intensity of two hydrogens, scalar coupled to H(2,3), has been identified at −7.43 ppm. The HSQC experiment reveals the tetrahedral nature of this carbon consistently with its 13 C chemical shift equal to 28.4 ppm. The analogous protonation of the internal C( 21) carbon has been previously detected for 21-carba-23-thiaporphyrin, 23 or β-alkylated 21-carbaporphyrin, 19 benzocarbaporphyrin, 49 and N-confused porphyrin.…”
Section: +mentioning
confidence: 75%
“…Here, it is essential to note that 15 and 16 potentially provide the core of a similar size but with different (−2 vs. −3) anionic charges. Still, complete characterization using the typical methodology (UV-vis, 1 H NMR, and 13 C NMR) was carried out, setting the spectroscopic reference point for further explorations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the vast class of carbaporphyrinoids, those incorporating two and more carbon atoms within the cavity remain rare. Examples of such systems include naphthiporphyrins, namely, carbaporphyrinoids incorporating at least one naphthalene moiety replacing the pyrrole ring in the porphyrin macrocycle. Recently, we have demonstrated that the horizontal expansion of the m -benziporphyrin , framework could provide the 28-hetero-2,7-naphthiporphyrins 1-X (X = S, Se, Te), which act as macrocyclic ligands for phosphorus­(V). , …”
mentioning
confidence: 99%